Matrix Hyaluronan-CD44 Interaction Activates MicroRNA and LncRNA Signaling Associated With Chemoresistance, Invasion, and Tumor Progression - Bourguignon, Lilly Y. W. (Frontiers in Oncology, 2019)
Tumor malignancies involve cancer cell growth, issue invasion, metastasis and often drug resistance. A great deal of effort has been placed on searching for unique molecule(s) overexpressed in cancer cells that correlate(s) with tumor cell-specific behaviors. Hyaluronan (HA), one of the major ECM (extracellular matrix) components have been identified as a physiological ligand for surface CD44 isoforms which are frequently overexpressed in malignant tumor cells during cancer progression. The binding interaction between HA and CD44 isoforms often stimulates aberrant cellular signaling processes and appears to be responsible for the induction of multiple oncogenic events required for cancer-specific phenotypes and behaviors. In recent years, both microRNAs (miRNAs) (with ~20–25 nucleotides) and long non-coding RNAs (lncRNAs) (with ~200 nucleotides) have been found to be abnormally expressed in cancer cells and actively participate in numerous oncogenic signaling events needed for tumor cell-specific functions. In this review, I plan to place a special emphasis on HA/CD44-induced signaling pathways and the presence of several novel miRNAs (e.g., miR-10b/miR-302/miR-21) and lncRNAs (e.g., UCA1) together with their target functions (e.g., tumor cell migration, invasion, and chemoresistance) during cancer development and progression. I believe that important information can be obtained from these studies on HA/CD44-activated miRNAs and lncRNA that may be very valuable for the future development of innovative therapeutic drugs for the treatment of matrix HA/CD44-mediated cancers.